2018
DOI: 10.1596/30863
|View full text |Cite
|
Sign up to set email alerts
|

Water Utility Turnaround Framework

Abstract: The World Bank does not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this work do not imply any judgment on the part of The World Bank concerning the legal status of any territory or the endorsement or acceptance of such boundaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Studies have shown that 25-50% of treated water is considered NRW due to deteriorating water distribution infrastructure, leakages, faulty billing systems, illegal connections, inaccurate water pressure management, and errors in metering, among other factors. This surpasses the World Bank recommendation of 25% of the total water produced, with many countries recording NRWs exceeding 60% [27]. In developing countries, about 45 million m 3 of water is lost daily, representing over USD 3B annually [28,29].…”
Section: Problem Statementmentioning
confidence: 95%
“…Studies have shown that 25-50% of treated water is considered NRW due to deteriorating water distribution infrastructure, leakages, faulty billing systems, illegal connections, inaccurate water pressure management, and errors in metering, among other factors. This surpasses the World Bank recommendation of 25% of the total water produced, with many countries recording NRWs exceeding 60% [27]. In developing countries, about 45 million m 3 of water is lost daily, representing over USD 3B annually [28,29].…”
Section: Problem Statementmentioning
confidence: 95%
“…On the one hand, they may be influenced by internal factors, such as the poor management of human resources or equipment, poor planning of maintenance and investment activities, or a lack of innovation and adaptation to new technologies. On the other hand, an inadequate economic policy, such as a low level of investment in infrastructure, for example the maintenance of low (populist) tariffs that do not cover the costs of drinking water production and wastewater treatment, can affect the performance of these utilities (Soppe, Janson, and Piantini, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The primary route for expanding services in urban areas is through public utilities, but utilities are struggling to deliver reliable services to connected households let alone increase coverage (Trimble et al, 2016;World Bank, 2017;Soppe et al, 2018). Revenue collection has become a major stumbling block for utility performance (Ahluwalia, 2002;World Bank, 2017).…”
Section: Introductionmentioning
confidence: 99%